Motifs et manifestations de l’amour de l’homme pour Dieu et l’amour du prochain selon Saint Basile le Grand - Ernest Janczyk (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
This article addresses the issue of the motivation of the fundamental order of love for God and the neighbour which Saint Basil the Great used in his doctrine. Based on an analysis of the texts of Saint Basil, this article demonstrates the intimate relationship that should exist between the love for God and the love for man. The ideal of this relationship is represented, according to the analysis, by Jesus Christ, the only Saviour of the world.